The role of sexism in holding politicians accountable for sexual misconduct - Longdon, Bella; Banducci, Susan (Frontiers in Political Science, 2023)
Experimental research on the impact of the #MeToo movement on the evaluation of politicians has focused on how the impact is conditioned by partisan motivation. Beyond partisanship, gender identity and sexist attitudes may also act as a barrier to the success of #MeToo in challenging sexual misconduct in politics. In a conjoint experiment, we examine the extent to which sexism and gender identities (feminine/masculine identity and self-identified gender) condition how individuals respond to politicians accused of sexual misconduct. Respondents were shown two profiles of fictional British male candidates accused of sexual misconduct where the characteristics of the candidate and the scandal were (the number of allegations made, whether they apologized for the misconduct, their partisanship, and their stance on Brexit). We find that in general, more severe misconduct has a more negative impact on evaluations but that respondents who expressed attitudes consistent with hostile sexism were less likely to punish politicians for multiple offenses and less likely to reward a recognition of wrongdoing. Categorical gender identity, whether the respondent was a man or a woman, did not condition the electoral consequences of the scandal and a feminine and masculine identities moderated the impact of the political stance of the candidate. We conclude by discussing the importance of measuring gender attitudes, especially sexism and non-categorical measures of gender identity, in future studies on the political consequences of #MeToo.